Prospects and barriers for development tourism in rural areas Warmia and Mazury - Iwona Batyk (Kazimierz Wielki University, 2011)
Warmia and Mazury have large European scale tourism and natural values. Attraction is the landscape of these areas, forests, lakes, clean natural environment, and numerous monuments of architecture and culture. The region is particularly well suited to the development of recreational functions, tourism, rural tourism and qualified - sailing, Horsemanship, hiking or cycling. The development of tourism in the world, that tourism is becoming one of the most important sectors of the economy for many countries. The authorities of the voivodship involve high hopes the development of tourism, seeing it as an opportunity for economic growth in the region. Tourism is a big area, but still unused opportunities of development for the voivodship. A major difficulty is the poor accessibility of the region, but also inadequate offer tourist and recreational facilities. The development of tourism in rural areas can significantly contribute to the creation of new jobs, allowing the region's economic development and meet the vital needs of its residents. In the current situation of tourism that brings an additional source of income for the population engaged in agriculture, but it certainly could become an alternative source of income for the ineffectiveness of many agricultural activities, especially small farms. Agrotourism is also the opportunity to develop other activities. Its development is mainly conditioned by the investment opportunities and promote the values of recreation in rural areas.